On the Kinetic Nature of Solar Wind Discontinuities - A. V. Artemyev; V. Angelopoulos; I. Y. Vasko; A. Runov; L. A. Avanov; B. L. Giles; C. T. Russell; R. J. Strangeway (Geophysical Research Letters)
Abstract The most intense currents in the solar wind are carried by magnetic field discontinuities. The formation of such structures depends on whether they are rotational or tangential discontinuities. To distinguish between these two types, variations of plasma characteristics should be studied. We analyze data from a set of discontinuities observed by the Acceleration, Reconnection, Turbulence, and Electrodynamics of the Moon's Interaction with the Sun and Magnetospheric Multiscale missions in the near‐Earth solar wind. We show that these discontinuities have properties characteristic of both tangential and rotational discontinuities: (1) Jumps in the tangential velocity component are well correlated with jumps in the Alfven speed, and (2) Electron density and temperature vary significantly across these discontinuities. Suprathermal electron pitch angle distributions change across discontinuities, revealing the importance of electron kinetics to discontinuity structure. Investigation of the discontinuity formation needs to go beyond magnetohydrodynamics theory and highly likely involves both ion and electron kinetics.